Real-time demands and calibration of water distribution systems. (November 2015) - Vassiljev, A.; Koor, M.; Koppel, T.
Abstract: All computer models of water distribution systems (WDS) have to contain information about demands. Usually demands are derived based on customer's water meters weekly or monthly readings. It gives information only about the average demand. Dynamics of hourly, daily and weekly demands are usually estimated based on typical demand patterns of different type of consumer groups like domestic households, hospitals or hotels. Estimation of demand dynamics by this manner inevitably decreases precision of calibration. Calculations show that differences between real-time and typical demand can influence results of calibration. The paper proposes some methods to minimize this influence. Special software has been developed for estimation of real-time water demands in a WDS. Algorithms and software checked on an operational WDS.